An exploratory clinical trial to evaluate the efficacy of an experimental dentifrice formulation in the relief of dentine hypersensitivity. (January 2017) - Parkinson, C.; Constantin, P.; Goyal, C.; Hall, C.
Abstract: Objectives: This study aimed to investigate whether addition of an octadecene/maleic anhydride copolymer (O/MA) to a potassium nitrate (KNO3 ) dentifrice could facilitate delivery of potassium to dentine and enhance its efficacy in dentine hypersensitivity relief. Methods: This was a randomised, examiner-blind, controlled, parallel group study in 139 healthy subjects with at ≥2 sensitive teeth. Assessment of dentine hypersensitivity to tactile (Yeaple probe) and evaporative (air) stimuli (Schiff Sensitivity Scale, visual analogue scale [VAS]) was carried out at baseline and after 1, 2, 4 and 8 weeks twice daily treatment with an experimental 5% KNO3 /3% O/MA dentifrice, a comparator 5% KNO3 dentifrice (active comparator), a 0% KNO3 /3% O/MA dentifrice (placebo) and a regular fluoride dentifrice (negative control). This study was not powered to detect statistically significant differences between treatments. Results: Across the treatment period an improvement in sensitivity to evaporative air stimulus was observed for all products and to a tactile stimulus for the potassium-containing treatments, with the greatest reductions for the experimental dentifrice (5% KNO3 /3% O/MA). Reductions in sensitivity observed for the potassium-containing dentifrices compared to the placebo and negative control dentifrices were statistically significantly for Schiff sensitivity score and tactile threshold at all time-points and for VAS at Weeks 4 and 8. Trends in the study data also favoured the experimental dentifrice, compared to the active comparator dentifrice, for all clinical measures. Study treatments were generally well tolerated. Conclusion: This study provides initial clinical evidence to suggest that addition of a polymer excipient may enhance the anti-sensitivity efficacy of potassium-containing dentifrices. Clinical significance: Daily use potassium-containing dentifrices are established as efficacious for the relief of dentine hypersensitivity. Inclusion of a polymer excipient in such formulations may facilitate delivery of potassium to the dentine surface and so enhance clinical efficacy. Further clinical studies are required to confirm this hypothesis.